Managing the patient with haemoglobinopathy and multiple red cell antibodies. (29th January 2016) - Politis, C.; Hassapopoulou, E.; Halkia, P.; Kourakli, A.; Mougiou, A.; Zervou, E.; Kleronomos, E.; Sfyridaki, K.; Pappa, C.; Tsoumari, I.; Lafiatis, I.; Kavallierou, L.; et al.
Abstract : Background and Objectives: Sickle cell disease (SCD) and thalassaemia, particularly the β‐type, represent major sources of morbidity. Recommended treatment includes regular blood transfusion following highly uniform strategies across thalassaemia units and monitoring related complications including alloimmunization. This complex problem depends on donor–recipient antigenic diversity, the patient's immune status and specific circumstances such as pregnancy. Materials and Methods: We examined alloimmunization against RBC antigens and autoimmunization in 983 patients with thalassaemia and SCD in Greece, in relation to applied RBC antigen matching policies and other factors possibly relevant in reducing the rate of alloimmunization and delayed haemolytic transfusion reaction (DHTR). Results: Up to 2010, 11.6% of all patients had history of alloimmunization and 7.3% of autoimmunization. Frequency was highest in thalassaemia intermedia followed by sickle–thalassaemia and thalassaemia major. New alloimmunization was low at 1.4% after 2010, corresponding to a risk of 1:9405 units of RBCs transfused. Despite the very high transfusion burden in the chronically transfused patients, the use of extended matched donor blood is proven effective in reducing the rate of alloimmunization. Conclusion: Multiple RBC alloantibodies represent a small but difficult to manage risk for responders prone to combination with autoimmunization. DHTR with hyperhaemolysis is a major clinical problem in haemoglobinopathies, especially during the gestational period and delivery in patients who escape expert medical follow‐up. Progress in the safety and quality of blood transfused in these patients is expected to contribute to prolongation of their life expectancy and to reproduction. Investigation of HLA and other antibodies in patients prone to developing RBC antibodies is suggested.